МУЗИЧНІ ЗДІБНОСТІ УЧНІВ В КОНТЕКСТІ ПРОБЛЕМИ ФОРМУВАННЯ ВОКАЛЬНО-ХОРОВИХ УМІНЬ (Педагогіка вищої та середньої школи, 2010)
This article is reflected the describes components of musical abilities of pupils that affect the quality of forming vocal-chorus abilities, within components musical Unities. discusses such a notion as "musical ear", "feeling rhythm", musical memory", examines the shortcomings of the musical ear.